Konstruk Pembelajaran Bahasa Arab Konstruktif dalam Lokus Merdeka Belajar-Kampus Merdeka: Perspektif Filsafat Konstruktivisme - Basir, Abdul; Rusydi, Muhammad (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2021)
Arabic learning which is developed in the concept of independent learning-independent campuse must provide a philosophical as well as methodical framework in strengthening the potential of students, especially in strengthening them to put Arabic and its learning as an active component of learning. In this proses, Arabic learning must be able to adopt the constructivism philosophy. In the process, learning Arabic must actively facilitate students to carry out various processes that enable them to construct the knowledge they have acquired during the learning process to later become new knowledge. This new knowledge can be constructed in different contexts.The learning paradigm that is promoted in the independent learning-independent campus must synergize optimally with the constructive Arabic learning paradigm both inside and outside the classroom.